IMPLEMENTASI KEBIJAKAN PENYALURAN BAHAN BAKAR MINYAK BERSUBSIDI DI KECAMATAN PONTIANAK TENGGARA - Antutn E.01107105, Erasmus Canaga (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This Scription is to described and analysis about behavior and implementation attitude from distribution BBM subsidy especially  the SPBU in South-East Pontianak, they are SPBU 61.781.01 Jl. A Yani, SPBU 64.781.01 Jl. Adi Sucipto Parit H.Husin 1, dan SPBU 64.781.11 Jl. Imam Bonjol. distribution oil of subsidy is done by PT. Pertamina Pontianak city Branch as the one of legal institute to funnel society that dispersed in variety place. Channelization system based on the substance of BBM available and will be given to SPBU as a request. There was nothing Channelization system socialization and the import of BBM to SPBU caused happened long stand in line of society to get BBM, needed monitoring and coordination between SPBU and PT. Pertamina. In this research, researcher used qualitative descriptive method.The result of this research show that first there have not been done any socialization  about channelization policy of subsidy BBM to SPBU, second there was nothing official of that,  and the tirth direct report are done by SPBU each commutation have permanent characteristic still do not help to avoid BBM scarcity at SPBU. There’s some suggestion in this research, first the active action from Implementator in give sosialisation  about channelization activity at SPBU and society, second the readiness from the seller that is SPBU in make a communication with PT. Pertamina in order to not make a scarcity of BBM, and third the channelization have to transparency and use distribution control process with automatic system from PT. Pertamina to SPBU. Keywords : Premium and subsidy